2004
DOI: 10.1111/j.1572-0241.2004.04127.x
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine to Treat Irritable Bowel Syndrome Not Responding to High-Fiber Diet: A Double-Blind, Placebo-Controlled Trial

Abstract: The difference in overall well-being found in our paroxetine/placebo trial is greater than that found in previously published drug/placebo trials for IBS. Moreover, the difference in well-being applied to nondepressed recipients of paroxetine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(111 citation statements)
references
References 14 publications
3
103
1
4
Order By: Relevance
“…It may be that specific subgroups of patients with functional dyspepsia, such as those with co-morbid anxiety or depression, would do well on one or both of these agents. Other evidence suggests that antidepressant therapy may improve global well-being rather than specific gastrointestinal symptoms in irritable bowel syndrome [22], and this could not be assessed in the current study model. However, any benefit of these drug classes in functional dyspepsia remains to be established by appropriately conducted, randomized, controlled trials.…”
Section: Discussioncontrasting
confidence: 40%
“…It may be that specific subgroups of patients with functional dyspepsia, such as those with co-morbid anxiety or depression, would do well on one or both of these agents. Other evidence suggests that antidepressant therapy may improve global well-being rather than specific gastrointestinal symptoms in irritable bowel syndrome [22], and this could not be assessed in the current study model. However, any benefit of these drug classes in functional dyspepsia remains to be established by appropriately conducted, randomized, controlled trials.…”
Section: Discussioncontrasting
confidence: 40%
“…Fewer studies have been conducted with SSRIs. In one randomized-controlled trial comparing paroxetine (10-40 mg/d) to placebo, patients treated with the SSRI reported a significant improvement in overall wellbeing, but did not experience improvement in abdominal pain [118] . Other studies with paroxetine have shown an improvement in abdominal pain and discomfort, and suggest that further studies with this class of medication are needed [119,120] .…”
Section: Antidepressantsmentioning
confidence: 99%
“…SSRIs may improve visceral hypersensitivity, particularly in constipationpredominant IBS, although the effi cacy of this class of medications continues to be debated [168,169] . Finally, SSRIs have been shown to improve patients' sense of well-being, even in non-depressed patients [170] .…”
Section: Irritable Bowel Syndromementioning
confidence: 99%